Effect of Nd Addition on the Microstructure and Martensitic Transformation of Ni-Ti Shape Memory Alloys - M. Dovchinvanchig; C. W. Zhao; S. L. Zhao; X. K. Meng; Y. J. Jin; Y. M. Xing (Advances in Materials Science and Engineering)
The effect of rare earth element Nd addition on the microstructure and martensitic transformation behavior of Ni50Ti50−xNdx (x=0, 1, 3, 7, 20) shape memory alloy was investigated experimentally. The results showed that the microstructure of Ni-Ti-Nd ternary alloy consists of the NiNd phase and the NiTi matrix. One-step martensitic transformation was observed in all alloys. The martensitic transformation start temperature Ms increased gradually with increasing Nd content for Ni-Ti-Nd alloys.